EFFECT OF EXTRACTION OF SHEEP MANURE WITH WARM WATER ON THE GROWTH AND NUTRIENTS CONTENT OF TOMATO PLANTS UNDER CULTIVATION OF PLASTIC HOUSES - & Al-Sulaimawi, Al-A’amry (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
An experiment was conducted under greenhouse condition at a farm located in AlImary district east of Baghdad to study the effect of sheep manure water extract on the growth of tomato plants var. Wijdan during the season of 2014-2015.The experiment was consisted of 14 treatments which included of sheep manure with hot (42ْC) and lmbient (20ْC) Water temperature applied either by foliar at 25% and 50% concentration or directly to the soil at 50% and 100% concentration splited to 7 applications control treatments either distilled water as foliar and recommended chemical fertilizers (applied to soil). The experiment was designed according to the random complete block statistical design (RCBD) with three replications Results showed that the chemical treatment and the treatment of hot water extracted significantly when compared with the cold counterpart especially the treatment of hot water extract sheep manure sprayed at 50% and soil applied at 100% concentration in plant height, leaf number, leaf area , plant dry weight and total chlorophyll. In addition, the chemical treatment and the treatment of hot water foliar applied at 50% and soil applied at 100% concentration significantly increased concentration of N ,P and K in leaf tissue while hot extract gave the highest Ca and Mg concentration in leaf tissue.